The Influence of Innovation Strategy and Company Efficiency on Competitive Advantage and Its Influence on the Performance of Residential Developer Companies in Central Java - Maulana, Dewanda; Hidayati, Retno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Problems in the performance of housing developer companies in Central Java, especially during the post-pandemic period. There are companies that have been affected by the consequences of the ongoing economic crisis, especially housing developer companies in the property sector in Central Java. Researching a sample of housing developer companies in Central Java that are members of the REI, which as a whole has 350 members. The structural Equation Modeling (SEM) method was adopted as software to assist in testing models and hypotheses. Structural Equation Modeling (SEM) analyzes 200 questionnaires that have been filled in by the top managers of the companies concerned. In this study there are findings that in achieving the performance of housing developer companies in Central Java can be achieved by increasing the company’s innovation and efficiency strategies both directly and through the company’s competitive advantage, then these results can be a consideration for housing developer businesses in Central Java in improving their performance. This study only uses indicators of efficient operational costs, efficient use of manpower, efficient use of work equipment, and efficient use of raw materials in the company efficiency variable. Meanwhile, efficiency indicators in terms of financial data and company assets cannot be accessed because some companies do not wish to provide confidential data. Future research is expected to use better-supporting data. There are managerial implications that can be utilized and studied by housing developer businesses. The study explains the influence of the company's innovation strategy and efficiency on company performance both directly and through competitive advantage. The conceptual model of this research was tested on a sample of housing developer companies in Central Java that are members of the Central Java REI association.